Prevalence and factors associated to the use of illicit drugs and psychotropic medications among brazilian undergraduates (Acta Scientiarum. Health Sciences, 2020)
The aim of this study was to verify the prevalence of use of psychoactive substances (PS) and its associated factors in undergraduate students of a university in southern Brazil. The study was carried out with 830 undergraduate students in the year 2016. The individuals answered a self-administered questionnaire about the PS and its prevalence of daily use, in the last 30 days or at any time of their lives, as well as socioeconomic conditions and academic variables. Caffeine-based energy drinks was the most consumed psychoactive substance (96.3%) among undergraduates in the last 30 days, followed by alcohol (64.0%). Among the illicit drugs most consumed in the last 30 days was marijuana (17.3%), while anxiolytics and amphetamines were the most prevalent psychoactive medicaments in the last 30 days. The prevalence of lifetime illicit drugs used by these students was 41.5%, where we highlight besides marijuana (38.6%) the high consumption of cocaine (7.8%), ecstasy (9.3%) and solvents. Socioeconomic and demographic factors such as gender, have children, religion, and financial background as well as academic variables were associated to recent consumption of these substances. This study concluded there is a high prevalence of use of PS among the undergraduate students, including illicit drugs.